Prevalence of breast cancer and its associated factors for recurrence in Hospital Tengku Ampuan Afzan from 2008 to 2012 - Azhani binti Chik (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Breast cancer is the commonest malignancy in Malaysian women. Cancer recurrence has been a detrimental factor towards survival with peak of recurrence recorded in first 2 years of diagnoses. Identifying the prognostic factors towards recurrence is important to management and prolonging survival. We have retrospectively analyzed 179 patients women with breast cancer based on 5 years single centre database with minimum follow up of 2 years. The demographic and clinicopathological characteristics were determined using descriptive statistics. Survival were calculated based on Kaplan- Meier method and multivariate analysis by Cox proportional hazards was performed to evaluate the potential factors affecting breast cancer recurrence. Mean follow up was 42 months, with mean age 52 years and 60.9% presented in Stage II disease. Overall recurrence was 41.9% with local recurrence 2.1%, regional recurrence 12.3% and distant recurrence 27.4%. 50% of our patients developed recurrence at 25 months. On univariate analysis, time to first presentation was significantly correlated with recurrence, while in multivariate analysis tumor size, lymph node positive and lymphovascular invasion were independently associated with recurrence.